Feature Writer 2013: Alice Garner - Team , Offset Editorial (Offset, 2013)
Alice Garner is a historian, musician, actor and writer. She has published two books, The Student Chronicles (MUP, 2006), a memoir of her undergraduate experience, and A Shifting Shore: Locals, Outsiders and the Transformation of a French Fishing Town, 1823-2000 (Cornell University Press, 2005), which was shortlisted for the NSW Premier’s General History Prize.